Digital Leadership at the Minahasa Regency Woman’s Empowerment and Child Protection Office - Herlina Gesri R. Sali',; Jetty E. H. Mokat,; Recky H. E. Sendouw, (Technium Social Sciences Journal, 2023)
The purpose of this examine is to discover and describe how digital leadership is within the ladies's Empowerment and infant protection workplace of Minahasa Regency. This research is a descriptive studies with a qualitative method. records series strategies thru observation, interviews, and documentation. The data evaluation techniques used are information reduction, facts presentation, and verification. The results of the study show that leaders at the Women's Empowerment and Child Protection Service have fairly good knowledge in the field of digital technology, are able to utilize digital technology in carrying out their duties and responsibilities as leaders, but are not optimal. Because there are still various obstacles or problems, including the inadequate availability of computer equipment, network problems, but also the existing human resources/employees are not all fluent in utilizing digital technology.